Simvastatin therapy in patients with hepatic disease - O. M. Drapkina; A. V. Klimenkov; I. I. Sukhovskaya; V. T. Ivashkin (Кардиоваскулярная терапия и профилактика)
Aim. To assess effectiveness, safety, and tolerability of simvastatin (Vasilip) in patients with IIa and IIb dyslipidemia, as well as with hepatic disease. Material and methods. The analysis included 30 patients receiving Vasilip (20 mg/d). At baseline and after 3, 6, and 14 months of the treatment, fasting levels of total cholesterol (TCH), triglycerides (TG), high-density lipoprotein CH (HDL-CH), low-density lipoprotein CH (LDL-CH), aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activity, bilirubin and creatinine were measured. Vasilip lipid-lowering effectiveness and tolerability was assessed during 12 months of the therapy. Results. After 12 months of Vasilip therapy, there was a significant reduction in TCH (17,5%), TG (26,3%), and LDL-CH (27,8%) levels; HDL-CH increase (23,3%) was not statistically significant. Atherogenicity index decreased by 36,7%. Vasilip therapy was well tolerated by individuals with hepatic pathology throughout the whole study. No significant increase in AST and ALT activity, glucose, creatinine or bilirubin levels was observed. Conclusion. Long-term (one-year) simvastatin therapy (20 mg/d) in patients with lipid hepatosis was both safe and clinically effective.